2016
DOI: 10.5194/nhess-16-1239-2016
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami hazard potential for the equatorial southwestern Pacific atolls of Tokelau from scenario-based simulations

Abstract: Abstract. Devastating tsunami over the last decade have significantly heightened awareness of the potential consequences and vulnerability of low-lying Pacific islands and coastal regions. Our appraisal of the potential tsunami hazard for the atolls of the Tokelau Islands is based on a tsunami source-propagation-inundation model using Gerris Flow Solver, adapted from the companion study by Lamarche et al. (2015) for the islands of Wallis and Futuna. We assess whether there is potential for tsunami flooding on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…Even though the bathymetry dataset used (Rasheed et al, 2020) is the highest resolution currently available for the Maldives, it is comprised of data from a variety of sources, and the defects of these datasets will manifest as defects in this study. We find that the bathymetry exerts a major influence in directing tsunami waves across the complex geometry of the atolls of the Maldives, in agreement with Orpin et al (2016), who showed similar effects in Tokelau in the Pacific. Availability of better bathymetry data, particularly near the coastline, can be used to further improve the model, and thus the collection of such data should be a priority for the Maldives as it will have clear and direct benefits for risk management across the archipelago.…”
Section: Limitations Of the Study And Recommendations For Improvementsupporting
confidence: 90%
See 1 more Smart Citation
“…Even though the bathymetry dataset used (Rasheed et al, 2020) is the highest resolution currently available for the Maldives, it is comprised of data from a variety of sources, and the defects of these datasets will manifest as defects in this study. We find that the bathymetry exerts a major influence in directing tsunami waves across the complex geometry of the atolls of the Maldives, in agreement with Orpin et al (2016), who showed similar effects in Tokelau in the Pacific. Availability of better bathymetry data, particularly near the coastline, can be used to further improve the model, and thus the collection of such data should be a priority for the Maldives as it will have clear and direct benefits for risk management across the archipelago.…”
Section: Limitations Of the Study And Recommendations For Improvementsupporting
confidence: 90%
“…Even where hydrodynamic simulations of such domains have been carried out, e.g. for Tokelau in the South Pacific (Orpin et al, 2016) and Xisha archipelago (also known as the Paracel Islands; Xie et al, 2019), complex multi-atoll interactions have not been considered. The Maldives archipelago, consisting of a string of multiple atolls, each characterized by many islands and bathymetric features, provides an excellent case study to assess tsunami propaga-tion in a complex multi-atoll system and learn how acrossatoll and within-atoll effects can influence the local impact of tsunamis.…”
Section: Introductionmentioning
confidence: 99%
“…that portion of the coast that is likely to be inundated (say less than 10 m above mean sea level) is most often lacking accuracy for the Pacific Island. The issue is of dramatic importance for low lying islands such as a number of Pacific atolls (Orpin et al, 2015) where the highest elevation is often more than 5 m above mean sea level. The elevation data we acquired for the coastal fringe in Wallis enabled us to calibrate the DTM and strengthen our models.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…This is critical for the numerous 2. low-lying islands of the Pacific which have not been the recipient of many tsunami hazard studies such as in Tokelau (Orpin et al, 2015) or in the Marquesas (Hébert et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the Pacific Islands region, far-field or distant-sourced tsunamis which take up to several hours from initiation to coastal impact are typically considered lower risk events compared with locally sourced tsunamis (e.g., [16]). However, there is a dearth in detailed hazard risk modelling studies which demonstrate the effects that SLR will have on exacerbating tsunami inundation risk to far-field events in Pacific Island environments.…”
Section: Introductionmentioning
confidence: 99%